2016
DOI: 10.1515/rnan-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of large RNA structures: learning from DNA nanotechnology

Abstract: growth of other materials, and as drug delivery vectors. Both RNA and DNA have been successfully used to build scaffolds with rationally programmable features. RNA structures up to a few hundreds of nanometers large have been demonstrated to assemble in vitro as well as in vivo [2,3]. DNA has however been the polymer of choice to demonstrate 2D and 3D self-assembled structures with size ranging from 20 nm to several microns, due to its stability and the predictability of Watson-Crick base pair interactions [4]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…Importing DNA nanotechnology design methods to RNA has the potential to yield increasingly complex and scalable nanostructures. Specifically, tile systems used in DNA nanotechnology could yield large RNA nanostructures, which may be useful in biomedical applications as delivery scaffolds for multiple nanoparticles 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Importing DNA nanotechnology design methods to RNA has the potential to yield increasingly complex and scalable nanostructures. Specifically, tile systems used in DNA nanotechnology could yield large RNA nanostructures, which may be useful in biomedical applications as delivery scaffolds for multiple nanoparticles 28 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, virus assembly must be fast in order to produce many virus particles before the infected cell is eliminated by the host’s immune system [14, 22, 37]. Moreover, as larger and ever more complex nanostructures are to be realized for technological or medical applications, time efficiency in artificial self-assembly becomes vital [7, 30]. Designing self-assembly schemes that are fast and resource efficient is, however, challenging.…”
Section: Introductionmentioning
confidence: 99%
“…What kinds of schemes optimize the assembly time? Answers to these questions will enable assembly strategies to be identified that are optimally suited for the production of large, functionally complex macromolecular structures via artificial self-assembly, a major goal in nanotechnology [5, 7, 24, 27, 30]. Here, we address these questions by studying the time complexity (as opposed to structural complexity [1, 6, 10, 29]) of four prototypical self-assembly scenarios, using scaling arguments and in-silico modelling of the stochastic dynamics (see Methods).…”
Section: Introductionmentioning
confidence: 99%
“…For example, virus assembly must be fast to produce many virus particles before the infected cell is eliminated by the host’s immune system ( 1 3 ). Moreover, as larger and ever more complex nanostructures are to be realized for technological or medical applications, time efficiency in artificial self-assembly becomes vital ( 4 , 5 ). Designing self-assembly schemes that are fast and resource efficient is, however, challenging.…”
mentioning
confidence: 99%
“…What kinds of schemes optimize the assembly time? Answers to these questions will enable assembly strategies to be identified that are optimally suited for the production of large, functionally complex macromolecular structures via artificial self-assembly, a major goal in nanotechnology ( 4 , 5 , 11 13 ). Here, we address these questions by studying the time complexity (as opposed to structural complexity) ( 14 17 ) of four prototypical self-assembly scenarios, using scaling arguments and in silico modeling of the stochastic dynamics.…”
mentioning
confidence: 99%